Children's perception of gender orientation based on a dancer's nonverbal communication - Almazan, Kristan Dalsi S.; Bagalay, Karla Nova Grace O.; Sanoy, Thierri Jeff A. (2011)
A child's perception is one of the most difficult yet interesting fields to study in the world of communication. A child has a complex and dynamic mind that tends to be influenced by the society and other social norms, especially on the area of sexuality and gender orientation. The study focused on the formative years of a child. It looked into the cognitive stencils and stereotypes the children have at that time in classifying a person as gay or straight and applying those stencils in the context of performance, particularly dance. The study generally answered the question why and how do children perceive a dancer's sexuality based on the nonverbal cues displayed and exhibited by a dancer. It also sought to answer what specific movements the children classify as something gay and something straight. Social norms can affect the perception of an individual. Thus, this study challenges the realm of stereotype on gender orientation and preference through the use of non-verbal communication. It has determined the reasons why some people are perceived to be "gay" through their gestures and other non-verbal cues. The study fills a gap in knowledge because, though we have accounts and theories to constitute the formative years of a child as a basis of gender norms, little of which were focused on the perception of a child to a dancer or performer. The study's framework of study started with the premise from Stanislavski's propositions. We assume that in that context we see the dancer to be merely like an actor in a performance who portrays a particular role near who he is. We see the dancer as a performer that persuades an audience to look at him as something he determines. A certain level of persuasion happens and the perception carries a certain level of judgement. With that, the study utilized two well known theories that fall under judgement and perception - the Social Judgement Theory by Muzafer Sherif and Elaboration Likelihood Model by Richard Petty and John Cacioppo. Basically, both theories cover the same concept and in fact one theory is a modification of the other. In that context we see dance as a performance containing nonverbal cues as a persuasive message and that we assume that the dancer is the medium of persuasive message on gender orientation. The research saw the gesture defined the movement of the dancers and consequently limited how the dancers moved therefore the dance genre defined the sexuality of the dancer and the dancer's actual sexuality did not necessarily reflect. The researchers was that the movement of a dancer does not affect how the respondents judged the dancers sexuality but the culture of dance itself played and even defined and limit the movement of the dancers. Furthermore some dances have actual roots, in one way or another, to sexuality and krump and vogue belongs to that classification of dance -- Author's abstract.
Thesis (Bachelor of Arts in Social Sciences) -- University of the Philippines Baguio, 2011.
Includes bibliographical references (leaves 52-54)
Keywords: Gender identity in dance; Identity (Psychology) in children; Body language; Perception in children